Relationship between the Farmers' Level of Compliance in Using Pesticides and Pests, Diseases, Natural Enemies and Product Safety of Rice - Amalia Rahmadani, Shinta; SHK, Suparman; Irsan, Chandra (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2024)
The use of pesticides is one of the control alternatives that is widely used by farmers. However, continuous and inappropriate use of pesticides can have negative impacts on humans and the environment. This research aims to determine the relationship between the level of farmer compliance in using pesticides and pest attacks, disease, natural enemy populations and product safety. The research was conducted in two areas, namely Tanjung Lago and Pemulutan by interviewing farmers and direct observation of rice fields. The variables observed were the percentage and intensity of pest attacks, plant disease. and natural enemy populations. The level of farmer compliance is connected to field data and the correlation efficiency is calculated. The relationship between farmer compliance in the use of pesticides against pests and disease is negatively correlated, and positively correlated with the population of natural enemies. Using herbal pesticides according to the dosage can reduce the negative impact of pesticides on the environment.